Systemic bone marker expression induced by grey and white mineral trioxide aggregate in normal and diabetic conditions - de Azevedo Queiroz, I. O. [UNESP]; Mello, W. G. [UNESP]; Martins, C. M. [UNESP]; Dal Fabbro, Renan [UNESP]; Narciso, L. G. [UNESP]; Massunari, L. [UNESP]; Cintra, L. T.A. [UNESP]; Ervolino, E. [UNESP]; Gomes-Filho, J. E. [UNESP] (My University, 2018)
Aim: To investigate the relationship between diabetes mellitus and local/systemic effects of both grey and white mineral trioxide aggregate (MTA) Angelus on bone marker expression. Methodology: Wistar rats were divided into two groups: healthy and diabetic (Alloxan induced), which were further divided into three subgroups (control, GMTA Angelus and WMTA Angelus). Polyethylene tubes filled with MTA materials or empty tubes were implanted in dorsal connective tissue. On days 7 and 30, blood samples were collected for calcium, phosphorus and ALP measurement. The animals were euthanized; implanted tubes were removed and processed for immunohistochemical analysis of osteocalcin (OCN) and osteopontin (OPN). Kruskal–Wallis followed by Dunn's multiple comparison test was performed for nonparametric data, and anova followed by Tukey's test for parametric data. Results: No difference in systemic serum calcium levels between both groups was observed. On day 7, serum phosphorus levels within the WMTA healthy group were higher than that of the diabetic group. On day 30, healthy rats exhibited lower phosphorus levels than diabetic ones. At both time points, the diabetic group was associated with more ALP activity than the healthy group. Immunohistochemical analyses of the healthy group revealed OCN- and OPN-positive cells in the presence of both MTA materials. However, under diabetic conditions, both OCN and OPN were absent. Conclusion: Both MTA materials were associated with an increase in serum calcium, phosphorus and ALP, suggesting a potential systemic effect, along with triggered differentiation of OCN- and OPN-positive cells. Moreover, in diabetic conditions, an inhibitory effect on MTA-induced differentiation of OCN- and OPN-positive cells was detected.
Keywords: alloxan; bone markers; diabetes mellitus; mineral trioxide aggregate